Mechanistic insights into dioxygen activation by a manganese corrole complex: a broken-symmetry DFT study. Issue 40 (16th July 2021) - Yu, Jiangfeng; Lai, Wenzhen
Abstract : DFT calculations revealed a novel mechanism for the formation of Mn(v )–oxo in the dioxygen activation by a Mn(iii ) corrole complex involving a Mn(iii )–alkylperoxo intermediate. Abstract : The Mn–oxygen species have been implicated as key intermediates in various Mn-mediated oxidation reactions. However, artificial oxidants were often used for the synthesis of the Mn–oxygen intermediates. Remarkably, the Mn(v )–oxo and Mn(iv )–peroxo species have been observed in the activation of O2 by Mn(iii ) corroles in the presence of base (OH − ) and hydrogen donors. In this work, density functional theory methods were used to get insight into the mechanism of dioxygen activation and formation of Mn(v )–oxo. The results demonstrated that the dioxygen cannot bind to Mn without the axial OH − ligand. Upon the addition of the axial OH − ligand, the dioxygen can bind to Mn in an end-on fashion to give the Mn(iv )–superoxo species. The hydrogen atom transfer from the hydrogen donor (substrate) to the Mn(iv )–superoxo species is the rate-limiting step, having a high reaction barrier and a large endothermicity. Subsequently, the O–C bond formation is concerted with an electron transfer from the substrate radical to the Mn and a proton transfer from the hydroperoxo moiety to the nearby N atom of the corrole ring, generating an alkylperoxo Mn(iii ) complex. The alkylperoxo O–O bond cleavage affords a Mn(v )–oxo complex and a hydroxylated substrate. This novel mechanism for the Mn(v )–oxo formation via an alkylperoxo Mn(iii ) intermediate gives insight into the O–O bond activation by manganese complexes.